2022
DOI: 10.3389/fendo.2022.1072647
|View full text |Cite
|
Sign up to set email alerts
|

A rare pituitary tumor associated with hyperthyroidism and acromegaly

Abstract: BackgroundMixed pituitary TSH/GH adenomas are rare adenomas associated with acromegaly and/or thyrotoxicosis, with or without varying degrees of goiter. In this report, we show a case of pituitary adenoma producing both GH and TSH simultaneously.Case presentationA 27-year-old man was diagnosed with pituitary adenoma based on various symptoms and clinical findings. For further examination and treatment, he was hospitalized in our institution. It was likely that this subject had pituitary adenoma producing both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
2
1
0
Order By: Relevance
“…Because of the obscure symptoms of inappropriate secretion of TSH and acromegaly, the ignorance and delayed diagnosis of disease often occurs. The major manifestations of the affected gonadal axis in our patients were central hypogonadism or reduced libido in the males and menstrual disturbance in the females, which was consistent with current reports ( 11 , 14 , 26 28 ). In view of the exclusion of mixed prolactinoma, the pituitary stalk effect might contribute to the slight elevation of PRL in two of our patients without any symptoms or signs of hyperprolactinemia.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Because of the obscure symptoms of inappropriate secretion of TSH and acromegaly, the ignorance and delayed diagnosis of disease often occurs. The major manifestations of the affected gonadal axis in our patients were central hypogonadism or reduced libido in the males and menstrual disturbance in the females, which was consistent with current reports ( 11 , 14 , 26 28 ). In view of the exclusion of mixed prolactinoma, the pituitary stalk effect might contribute to the slight elevation of PRL in two of our patients without any symptoms or signs of hyperprolactinemia.…”
Section: Discussionsupporting
confidence: 93%
“…Similar to previous studies, the major manifestations of GH/TSH coexisting PAs include acromegaly, hyperthyroidism with or without goiter, the mass effects of tumors and other axes involved ( 11 , 13 15 , 17 , 21 ). Although the most common first symptom was hyperthyroidism, their thyroid antibodies were negative, and a series of symptoms frequently observed in thyroid disease did not occur in these patients, such as exophthalmos and mucous edema.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This may be explained by hyperthyroidism, which contributed to the increase in metabolism by increasing the speed of the basal metabolic rate in the body by stimulating cellular oxidation through high consumption of mitochondrial oxygen with increased expression of Na+ / K+ATPase, an enzyme that carries out the active transport of potassium and sodium in opposite directions, as it derives the necessary energy for this from the decomposition of ATP molecules [27], high rates of carbohydrate and lipid metabolism as well as the destruction of proteins, including carbonyl protein, a protein produced from the oxidation of proteins inside cells as a result of damage to enzymes by oxidative stress, which is associated with high oxygen consumption, which constitutes a risk factor resulting in increased oxidation inside cells in conjunction with the high level of free radicals, which causes oxidation of many biomolecules as well as DNA damage and lipid peroxidation resulting from an imbalance between oxidants and antioxidants, as the high level of oxidants is accompanied by a decrease in antioxidants it is a state of oxidative stress that results in an imbalance between ROS and the body's ability Bioassay on the detoxification of reactive intermediates that result in damage to organ tissues [28]. On the other hand, the results showed a significant increase in the level of antioxidants SOD, GSH and CAT accompanied by a decrease in the level of MDA in the aggregates that were treated with free and nano-drug, and this improvement may be explained by the role of free and nano-drug in regulating the level of thyroid hormones, which contributed to regulating the level of hydroxyl radical (OH -) and hydrogen peroxide H2O2 and superoxide ion (O2-) in the liver, causing a balance of cellular and enzymatic oxidation and reduction processes with a high level of antioxidants, thereby reducing therefore, the decrease in the level of SOD, GSH and CAT in the totals treated with thyroxine is attributed to their role in preventing oxidation The study of Bednarek and his group (2004) confirmed that the treatment of patients with toxic multinodular Goiter and Graves 'disease with propylthiouracil contributed to reducing the level of hydroxyl radical, hydrogen peroxide and superoxide ion and then scavenging free radicals, while confirming that the treatment of patients with toxic multinodular Goiter and Graves' disease with propylthiouracil contributed to reducing the level of hydroxyl radical, hydrogen peroxide and superoxide ion and the study of [29] that the dosing of mice with thyroxine at 0.1 mg /kg body weight contributed to an increase in the level of the radical H2O2 and Ion (O2-), also explains the improvement in The groups that dosed Omega-3 to the role of long-chain unsaturated fatty acids represented by EPA, ALA and DHA in promoting the synthesis of antioxidants, including SOD, which converts the superoxide negative superoxide radical to hydrogen peroxide and then converts the cat radical H2O2 to water and oxygen, while GSH is inside the cells either in the form of oxidized disulfide (GSSG) or in the case of reduced glutathione, as its level is inversely correlated with the state of oxidative stress [30], a series of studies conducted on women with breast cancer confirmed that the intake of Omega-3 acids before and after chemotherapy contributed to an increase in their antioxidants, which enhanced the body's defence capabilities [31].Table (2) .…”
Section: The Level Of Antioxidantmentioning
confidence: 87%
“…Серед причин, що викликають гіпотиреоз по всьому світі є дефіцит йоду, а у регіонах, де споживається достатня кількість йоду, найбільш Журнал «Перспективи та інновації науки» (Серія «Педагогіка», Серія «Психологія», Серія «Медицина») № 3(37) 2024 поширеною є хвороба Хашимотоаутоімунне захворювання [4,5]. Обидва порушення можуть спостерігатися при порушенні регуляції ЦНС [6,7 ]. Відомо, що при гіпер-і при гіпофункції ЩЗ спостерігаються порушення когнітивної активності головного мозку [3].…”
unclassified